Potensi Fitokimia Daun Sirsak (Annona muricata L.) dan Daun Kemangi (Ocimum basilicum L.) serta Kombinasinya - Ramadhani, Selvia; Mulia, Melindra (Lembaga Yasin AlSys, 2025)
Medicinal plants are species that contain active compounds in part or all of their structures and can be utilized for therapeutic purposes. Soursop (Annona muricata L.) and basil (Ocimum basilicum L.) are two well-known medicinal plants containing secondary metabolites with potential therapeutic effects. This study aims to identify the classes of secondary metabolites present in soursop leaf extract, basil leaf extract, and their combination through phytochemical screening tests. The screening methods involved tests for flavonoids, alkaloids, terpenoids, steroids, saponins, and phenols. The results showed that both soursop and basil leaf extracts tested positive for flavonoids, phenols, steroids, and terpenoids. However, the combined extract only showed the presence of flavonoids and phenols. The differences in secondary metabolite composition in the combined extract suggest potential interactions between compounds that may influence the pharmacological effectiveness of each plant. This research contributes to an initial understanding of phytochemical interactions in combined medicinal plant formulations.